An effect of. Linguistic experience - auditory word discrimination by native and non-native speakers of Hindi - Sinha, Ashok Kumar (Journal of All India Institute of Speech and Hearing)
Speech audiometry h become an integral part of the audiologic and otolo ic diagnosis of he3.ring impairment during last 25 years (Goetzinger, 1978). Speech audiometry is extremely helpful in identification, diagnosis and specification of site of lesion in hearing impairments.